An Investigation of Academic Accountability among Student-Athletes - Sailes, Gary A. (My University, 1993)
This investigation examined the degree of control that college studentathletes felt they had regarding their academic experiences. The author developed a questionnaire and administered it to 918 male athletes at over 100 Division I institutions. Findings indicated that student-athletes have high academic aspirations but face structural as well as personal obstacles in maintaining control over their academic experiences. Time demands of their sports, lack of high school preparation, and inadequate personal study habits collectively contribute to the academic problems experienced by student-athletes. In addition. partial qualifiers under Proposition 48, All-American student-athletes, and white student-athletes demonstrate morecontrol over and more seriousness about their academic experiences when compared to Proposition 48 full qualifiers, all other student-athletes, and black student-athletes, respectively.
Keywords: academic performance; skills